2015
DOI: 10.1016/j.jhep.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure following atorvastatin dose escalation: Is there a threshold dose for idiosyncratic hepatotoxicity?

Abstract: The bulk of hepatotoxicity (drug induced liver injury, DILI) cases in clinical practice is idiosyncratic in nature. This assumption is based on the apparent absence of dose dependency and the unpredictability of the reaction, which presents after a relatively long latency period of drug exposure in susceptible individuals. Recent evidence suggests that the administration of high oral daily dose of drugs that undergo extensive hepatic metabolism does influence the risk of developing idiosyncratic DILI (IDILI) [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 9 publications
1
39
0
3
Order By: Relevance
“…The discordance between the publication and the registration information might decrease the validity of their findings [2]. Whether or not the high recurrence rate (68.9%) after PH affected RFS was not reported by Yin et al…”
Section: Referencesmentioning
confidence: 97%
See 1 more Smart Citation
“…The discordance between the publication and the registration information might decrease the validity of their findings [2]. Whether or not the high recurrence rate (68.9%) after PH affected RFS was not reported by Yin et al…”
Section: Referencesmentioning
confidence: 97%
“…Furthermore, the mean age in the far eastern population was 52 and 54 years for the partial hepatectomy patients and TACE patients, respectively. This compares with a median age of 69.9 years in the study from the Newcastle group [2]. Excluding patients 70 years or older is likely to have introduced a selection bias to the study, since older patients are more likely to have significant co-morbidities that would preclude major liver resection.…”
mentioning
confidence: 90%
“…Clinical practice guidelines for HCC state that drug-eluting beads (DEB) had similar response rates when compared with conventional TACE [1]. However, DEB is recommended for its less systemic adverse events.…”
mentioning
confidence: 99%
“…Qing Pang and his associates stated in their letter that patients with a high preoperative PLT had significantly worse OS and recurrence free survival (RFS). This statement was based on a small sample size, retrospective clinical study, which was recently reported [1]. A careful look at this retrospective study [3] showed aspartate amino-transferase to platelet ratio (APRI) but not PLT, to be associated with poor prognosis in patients with HCC.…”
mentioning
confidence: 99%
“…To the Editor: We read with great interest the letter by Kopp et al regarding our study on machine perfusion of rat livers, donated after cardiac death (DCD). Our goal was to compare the two main liver perfusion techniques, normothermic (NMP) and hypothermic oxygenated perfusion (HOPE) in terms of liver function and injury in a transplant model, closely adapted to the clinical situation [1].…”
mentioning
confidence: 99%